If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23t + -31 = 3t + -15 Reorder the terms: -31 + 23t = 3t + -15 Reorder the terms: -31 + 23t = -15 + 3t Solving -31 + 23t = -15 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -31 + 23t + -3t = -15 + 3t + -3t Combine like terms: 23t + -3t = 20t -31 + 20t = -15 + 3t + -3t Combine like terms: 3t + -3t = 0 -31 + 20t = -15 + 0 -31 + 20t = -15 Add '31' to each side of the equation. -31 + 31 + 20t = -15 + 31 Combine like terms: -31 + 31 = 0 0 + 20t = -15 + 31 20t = -15 + 31 Combine like terms: -15 + 31 = 16 20t = 16 Divide each side by '20'. t = 0.8 Simplifying t = 0.8
| -3+(-6p)=3(5+4p) | | 4(x+1)-2(2x-3)=10 | | 8(t-2)+4t=6(2t+2)-10 | | 5=f-19 | | 32x-6=14 | | 3x+12-9x=11-6x | | (7x-8)= | | 4x+y=-23 | | 3/4b-7=8 | | -8+(1r)=8(r-1) | | Y^2+10y+35=0 | | 9x+10-7x-4= | | 7*11= | | y=(9x+7)(x-3) | | 2(3a-9)=2a-1x(a-1) | | 4x^3+16x^2-8x= | | 14-19x+3x^2=0 | | -x/5+2=x/5+7 | | 7-5/2x=9 | | -24*2= | | X+2x+c=43 | | -81+6x=x+39 | | 5(y+1)=-8 | | 3c-2=8 | | -7x+8+4x=-3(x-3)-1 | | N=24 | | X+74=146 | | X-23=0 | | 7+10+x=2x+26 | | 5x=25-x | | 630/10 | | x+x+1=-222 |